Sosialisasi Pengenalan Bahan Tambahan Pangan pada Mitra Komunitas Laskar Belajar Malang - Wijaya, Dika Putra; Utomo, Yudhi; Putri, Ade Elviana; Etia, Chantiquenya Putri; Yudhowati, Nuraini Rachma (Universitas Methodist Indonesia, 2024)
The aim of community service is to provide education to members of the Laskar Belajar community in Malang City to provide education regarding healthy and safe food. Determining the quality of food ingredients that are often found depends on several determining factors, such as texture, taste, nutritional value and microbiological properties. Apart from that, there are factors that determine the quality of food, indicators of freshness and maturity in the food, so that it can be processed so that the quality of the food can also improve. The implementation method for community service is through outreach regarding food additives by providing several materials related to food additive solutions, especially for Laskar Belajar community partners in Malang City. The conclusion of this community service activity is that reducing the consumption of food additives (BTP) is very supportive in efforts to reduce the dangers when using these ingredients, because they can be detrimental to consumers.